1996
DOI: 10.3109/10731199609118891
|View full text |Cite
|
Sign up to set email alerts
|

Study of Therapeutic Efficiency of New Blood Substitutes in Experimental Hemorrhagic Shock

Abstract: In experiments on dogs, which were anesthetized and underwent hemorragic shock, the hemodynamics, oxygen transport and acid-base status were studied. Cardiac function was studied using ultrasound equipment. It was established that administration of Volekam and Polyoxidin corrects hypovolemia with subsequent restoration of arterial pressure in the aorta and cardiac cavities and increase in the myocard contractility and cardiac output. Comparative analysis has shown that Polyoxidin exerts a more prolonged action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although the management of shock is generally guided by hemodynamic considerations, reports suggest that the true aim of therapy should be the optimization of oxygen delivery (1). Consequently, a number of oxygen‐carrying products have been developed and tested for their ability to either augment or replace these first response resuscitative solutions in both preclinical (2–10) and clinical hypovolemic settings (11,12). This work has shown that a complete resuscitation fluid should possess colloidal properties necessary to maintain blood pressure while delivering oxygen to vital peripheral ischemic tissues.…”
mentioning
confidence: 99%
“…Although the management of shock is generally guided by hemodynamic considerations, reports suggest that the true aim of therapy should be the optimization of oxygen delivery (1). Consequently, a number of oxygen‐carrying products have been developed and tested for their ability to either augment or replace these first response resuscitative solutions in both preclinical (2–10) and clinical hypovolemic settings (11,12). This work has shown that a complete resuscitation fluid should possess colloidal properties necessary to maintain blood pressure while delivering oxygen to vital peripheral ischemic tissues.…”
mentioning
confidence: 99%